107k views
0 votes
Derivative using direct definition of derivative 2-x/2+x

1 Answer

3 votes

Let f(x) = (2 - x)/(2 + x). By definition of the derivative,


\displaystyle f'(x)=\lim_(h\to0)\frac{f(x+h)-f(x)}h


\displaystyle f'(x)=\lim_(h\to0)\frac{(2-(x+h))/(2+(x+h))-(2-x)/(2+x)}h


\displaystyle f'(x)=\lim_(h\to0)\frac{((2-x-h)(2+x)-(2-x)(2+x+h))/((2+x+h)(2+x))}h


\displaystyle f'(x)=\lim_(h\to0)(-4h)/(h(2+x+h)(2+x))


\displaystyle f'(x)=-4\lim_(h\to0)\frac1{(2+x+h)(2+x)}=\boxed{-\frac4{(2+x)^2}}

User Vijay C
by
5.9k points